Bounds for axially symmetric linear perturbations for the extreme Kerr black hole - Dain, Sergio Alejandro (2015)
We obtain remarkably simple integral bounds for axially symmetric linear perturbations for the extreme Kerr black hole in terms of conserved energies. From these estimates we deduce pointwise bounds for the perturbations outside the horizon.